Analysis of Communication and Public Services in Implementing Transparency of Job Vacancies Information on Instagram @pjkusu - Putri Munawwarah; Pohan, Syafruddin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Transparency in public services is something that shows the existence of truth and justice. Truth and justice can improve an agency's self-image and can gain full trust from the public. Moreover, transparency of job vacancies is what society needs most at this time. The aim of this research is to analyze @pjkusu Instagram uploads in implementing job vacancy information transparency and describe communication and public services in implementing job vacancy information transparency on @pjkusu Instagram based on the manager's perspective. This research uses qualitative methods with a focus on observation, in-depth interviews and literature study. The results of this research are that the Instagram account @pjkusu has implemented transparency in job vacancy information because the information is uploaded directly from the direction of the company providing the job vacancy.